Effect of Cu Preferential Orientation on the Microstructure and Properties of Anodized CuxO Films. Issue 3 (8th January 2020) - Gao, Zhaoqing; Cao, Jinwei; Wang, Chen; Chen, Yinbo; Muzammal, Hussain Muhammad; Wang, Weiqiang; Sun, Hao; Ma, Haitao; Wang, Yunpeng
Abstract : In this paper, in order to explore the effect of the preferential orientation of Cu on the preparation of robust anodized Cu2 O films, three types of Cu substrates with three different preferential crystal plane orientation [(111), (200), (220)] are employed. First‐Principles calculation is employed to calculate the surface energy of different Cu crystalline planes by the software of DACAPO, which is conducted by the plane‐wave pseudo‐potential method. The influence of the preferential plane orientation of Cu on the anodized oxidation reaction process and the morphology of anodized Cu x O films has been discussed in detail. The results indicate that the morphology of anodized Cu x O films depends on the preferential exposing plane orientation of Cu substrates under the same anodized oxidation condition. The high surface energy of Cu makes Cu atoms release more easily from lattices, leading to more different active‐reaction sites. Abstract : The morphology of anodized Cu x O films depends on preferential plane orientation of Cu. The high surface energy of Cu makes Cu atoms release more easily from lattices, leading to more different active‐reaction sites. The XPS results confirmed that the anodized Cu x O films consisted of CuO and Cu2 O.